PEMBINAAN SEKOLAH MINGGU BUDDHA DI VIHARA BUDDHA DHARMA DAN 8 PHO SAT - Saputro Edi Hartono (Yayasan Education and Social Center, 2023)
The establishment of Buddhist Sunday Schools in Dharma Buddhist Vihara and 8 Pho Sat aims to increase the spiritual understanding and awareness of Buddhist children and adolescents. This activity is done through teaching about Buddhism, meditation practice, and good character development. In addition, this dedication also aims to strengthen the relationship between the community and the Dharma Buddhist Temple and 8 Pho Sat as a center of religious activities. The method used in this activity is to deliver material interactively and provide case examples that are relevant to everyday life. The results of this activity are expected to provide benefits for participants in terms of religious understanding and practice and strengthen the relationship between the community and their places of worship. Buddhist Sunday school formation activities at Dharma Buddhist monasteries and 8 Pho Sat are in accordance with the Buddhist Sunday school schedule. Based on this, the implementation of this activity was carried out on Sunday, December 20, 2020. The participants were 31 Sunday school children consisting of 5 kindergarten students, 18 elementary school students, 6 junior high school students, and 2 vocational students. Activities consist of lectures or material presentations by lecturers adjusted to the level of education, devotional worship and meditation practices, and simulations of cohesiveness or teamwork. The practical material presented, participants were very enthusiastic about following every instruction delivered. Participants perform devotional worship and meditation in this activity. Evaluation of this activity is carried out by direct observation and question and answer. Thus it can be concluded that practical activities, participants are able to follow and practice them well